2020
DOI: 10.7705/biomedica.4780
|View full text |Cite
|
Sign up to set email alerts
|

El estrés crónico como mediador de la relación entre la posición socioeconómica y el cumplimiento del tratamiento farmacológico de pacientes hipertensos

Abstract: Introducción. La hipertensión arterial sistémica es un problema de salud pública en el mundo. En Colombia, su prevalencia es del 25 % y la mortalidad es alta. Los factores psicosociales que afectan el cumplimiento del tratamiento farmacológico no han sido estudiados suficientemente. En otros países, se ha estudiado el papel del estrés crónico en la relación entre la posición socioeconómica y el cumplimiento del tratamiento farmacológico antihipertensivo.Objetivo. Examinar el papel del estrés crónico como media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…There are limited data on rates of adherence in Colombia, but one cross-sectional study conducted among 258 patients with hypertension aged 45–70 years in Medellín, Quibdó, and Bogotá reported that only 27% were compliant with treatment [ 50 ]. Higher socioeconomic status was associated with better adherence, and chronic stress was associated with worse adherence [ 50 ].…”
Section: Issues In Hypertension Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…There are limited data on rates of adherence in Colombia, but one cross-sectional study conducted among 258 patients with hypertension aged 45–70 years in Medellín, Quibdó, and Bogotá reported that only 27% were compliant with treatment [ 50 ]. Higher socioeconomic status was associated with better adherence, and chronic stress was associated with worse adherence [ 50 ].…”
Section: Issues In Hypertension Managementmentioning
confidence: 99%
“…There are limited data on rates of adherence in Colombia, but one cross-sectional study conducted among 258 patients with hypertension aged 45–70 years in Medellín, Quibdó, and Bogotá reported that only 27% were compliant with treatment [ 50 ]. Higher socioeconomic status was associated with better adherence, and chronic stress was associated with worse adherence [ 50 ]. Similarly, a study in 500 Colombian patients with hypertension or type 2 diabetes found that adherence was worse among those with low socioeconomic status and those who had subsidized healthcare [ 51 ].…”
Section: Issues In Hypertension Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Los niveles de significación se determinaron a partir de un valor de 'p' menor o igual a 0,1 dadas las características de medición de las variables de interés y el tamaño de la muestra, tal como se ha utilizado en otros estudios (28,29). Los datos se analizaron con el software Stata 14™.…”
Section: Análisis Estadísticounclassified
“…Many healthcare professionals were concerned about the emotional health of adults with chronic illness at the outbreak of the pandemic [ 6 , 7 ]. Stress and anxiety are well-known risk factors for maladaptive coping (smoking, substance use, unhealthy eating habits and sedentary behavior) [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ], inadequate treatment adherence [ [18] , [19] , [20] , [21] , [22] ], reduced self-efficacy [ [23] , [24] , [25] ], avoidance of healthcare visits [ [26] , [27] , [28] ], and worse health outcomes [ [29] , [30] , [31] ]. In addition, the potential negative health consequences associated with limited availability and access to healthcare services were cited as a significant concern [ 32 ].…”
Section: Introductionmentioning
confidence: 99%